PENGINTEGRASIAN BUDAYA LOKAL BESEMAH KEDALAM MATERI SASTRA DI STKIP MUHAMMADIYAH PAGARALAM - Rohani, Tri; Pratama, Yoga (UNIB Press, 2021)
This research is a Research & Development which aims at investigating the development of instructional materials based on local wisdom. The materials developed were designed from the result of the students’ need analysis and teacher specialist’ interview at STKIP Muhammadiyah Pagaralam in Introduction to Literature subject and validated by experts. The research data were collected from student’s questionnaire, specialist’s interview and experts’ validation. Regarding the data of the students’ questionnaire which consisted of 35 students, it was found that most of the students were interested in literature but they found problems such as; the language of the texts, unfamiliar literary texts, difficult in appreciating the texts and lack of skill in writing literary text. However, according to them local wisdom was very important to be developed beside to preserve and enrich students’ knowledge about the culture of the local area also to help students comprehend the materials as well. Besides, students also needed bigger text and more work sheets in the modul. This finding was also in line with the lecturer specialist’s interview which was described qualitatively in which it explained that local wisdom can be such a good alternative literary materials in teaching learning process to help students comprehend the texts used. Based on expert validation, local wisdom materials also gave an extra point in the materials developed. Expert validation stated that from the whole aspects of validation, the development of the materials met very good criteria and met the students’ need.